Back from Westminster : British Members of Parliament and Their Constituents - Norton, Philip (Book collections on Project MUSE., 1993)
The British House of Commons has entered a period of substantial change, moving from a state of party cohesion and party leadership toward a more individualistic and active policy-making role. In the dynamic look at the British Parliament and its members, Philip Norton and David M. Wood highlight that change to more intensive constituency response and service on the part of individual members. Like members of the U.S. Congress, British Members of Parliament (MPs) are elected to represent geographical districts. The relationship between the MP and the constituency in Britain has become more impo.